1994
DOI: 10.1037/h0079524
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and refusal rights in mental health: Therapeutic justice and clinical accommodation.

Abstract: The impact of recognition by courts and legislatures in the 1970s and early 1980s of patients' rights to receive or to refuse mental health treatment is evaluated. The implementation of these rights in practice does not appear to have exerted an unduly disruptive or destructive effect on mental health services or their clienteles. At the same time, their recognition has not led to the salutary therapeutic jurisprudence envisioned by their proponents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…27. Therapeutic jurisprudence ('TJ') aims to craft laws and procedures which maximise therapeutic gains and minimise avoidable harms (Kapp, 1994;Slobogin, 1995;Wexler, 1992;Winick, 1994 , 1995), however, it also found that 'legal representation did not significantly increase patients' chances of successful discharge but did delay the hearings'. 31.…”
Section: Which Options Are Feasible?mentioning
confidence: 96%
“…27. Therapeutic jurisprudence ('TJ') aims to craft laws and procedures which maximise therapeutic gains and minimise avoidable harms (Kapp, 1994;Slobogin, 1995;Wexler, 1992;Winick, 1994 , 1995), however, it also found that 'legal representation did not significantly increase patients' chances of successful discharge but did delay the hearings'. 31.…”
Section: Which Options Are Feasible?mentioning
confidence: 96%
“…The recognition of clients' right to refuse treatment does not necessarily mean that their better interests are served. Indeed, clients' health status may be poorly served by exercising their right to refuse treatment (Kapp, 1994). Client refusals should not be met with punitive responses or a professional refusal to provide services in the future when a client reapplies.…”
Section: Freedom To Choose and Refuse Treatmentmentioning
confidence: 96%
“…The theoretical underpinnings of a right to services in the community are found in the early cases that established both a right to treatment and a right to the least restrictive alternative in commitment decision making (Kapp, 1994, this issue; Rhoden, 1982). These cases (Lessard v. Schmidt, 1972; O'Connor v. Donaldson, 1975; Wyatt v. Stickney, 1971, 1972, 1974) established the basic principles that served as groundwork for the attempt to structure a right to deinstitutionalization and to community services (Perlin, 1980).…”
Section: Development Of Right To Services*mentioning
confidence: 99%